Indeks Kesesuaian Wisata Air Terjun Perjiwa di Kabupaten Kutai Kartanegara - Noorsheha Noorsheha; Muhammad Yasser; Rifka Aresa Aulia Novana (Universitas Mataram, 2026)
This study aims to analyze the level of tourism suitability and area carrying capacity as an ecological basis for managing the Perjiwa Waterfall tourism area in Kutai Kartanegara Regency. The research was conducted using a quantitative descriptive approach through field observations, spatial mapping, measurement of physical environmental parameters, and distribution of structured questionnaires to 33 visitors. Data analysis included the calculation of the Tourism Suitability Index (TSI) for three recreational activities and the Area Carrying Capacity (ACC) based on spatial-temporal limits. The results revealed that before the rain, the tourism suitability index for sitting/relaxing and viewing scenery was classified as highly suitable (S1), while water activities were classified as suitable (S2). However, after rainfall, the suitability for water activities significantly dropped to unsuitable (S3) due to a drastic increase in turbidity and water current velocity. The ecological carrying capacity calculation showed that the maximum threshold of visitors that the ecosystem can accommodate is 858 people per day across all activities. Management recommendations focus on implementing a strict daily visitor quota and early warning systems during adverse weather to maintain ecological sustainability and visitor safety.